A Mathematical Model for Oceanic Circulation at "El Niño" Phenomenon - Rubio, Obidio (2018)
We describe a model that interprets the circulation of the tropical ocean in the periods when the meteorological phenomenon known as "El Niño" appears; A study area is defined as being the equatorial pacific, the ocean current is described by the primitive equations, which consists of the equations of motion and temperature transport which are strongly coupled. As boundary conditions, the wind stresses on the surface of the ocean is fundamental for the warming of waters, which due to its high variability we consider it random and described by a multiplicative white noise, generating the so-called stochastic primitive equations for the circulation of the tropical ocean.The variational formulation of the problem is presented and some estimates that allow verifying the existence of solutions of these equations.